HOW TO EVALUATE A PROGRAM WRITTEN BY CHILDREN: A PROGRAM EVALUATION SUPPORT TOOL FOR ELEMENTARY SCHOOL TEACHERS - Fukunaga, Rie; Sasaki, Hitoshi; Hanis, Ilyani Binti Mazlan (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Programming education will be an obligation at primary school in Japan starting in 2020. This leads elementary school teachers evaluate programs that are created by the students. However, a clear standard of evaluation which is necessary for teachers as an evaluation guidance has not been stipulated yet. The programming obligation will surely give a big burden to the them. Therefore, we are developing an application that support program evaluation, which can support teachers in evaluating programs created by children and enable to connect with the future guidance.A Program created by the children using Scratch will be read as an image and analyzed according to the evaluation item using template matching. By presenting materials to support evaluation using an application to the teachers, it can reduce their burden. In addition, by converting the results into data, it is easier to judge whether or not the children understand the content of the lesson, the teachers can respond to the children who cannot follow the class at an early stage.